A Progressive Force in Finnish Schooling?: Finland’s Education Union, OAJ, and Its Influence on School-Level Education Policy - Nivanaho Nina; Thrupp Martin (Springer, 2025)
The Trade Union of Education in Finland, OAJ, is a large organisation covering early childhood education through to adult education and training. OAJ claims to have a key role in influencing education policy and often takes up progressive stances in the media. At the same time, there has been little evidence of it contesting government policy in any overt way. To explore whether OAJ really influences Finnish education policy and in what ways, this chapter looks at education policy concerning comprehensive schooling during the period of the centre-right Sipilä Government in power from 2015–19 and then at the interests and responses of the OAJ over the same period. Employing a thematic analysis of OAJ press releases and other publications, the authors argue that whereas the Sipilä Government’s education policy emphasised a more neo-liberal and individualistic approach to educational equity, the OAJ often sought to highlight a version of educational equality and its challenges associated with a democratic ideal of social justice. The OAJ also sought a longer-term perspective in Finnish education politics than was manifested in the various projects of the Sipilä Government. Overall, the chapter provides insights into Finnish education policy-making processes that involve decision-makers and working groups operating at both national and local (municipal) levels and the related positioning of the OAJ.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling